Cultures et cheptels 1990-2019 - Confins (Confins)
The Brazilian Institute of Geography and Statistics (IBGE) published in October 2020 its annual information on the production of livestock and agriculture in the country, the Pesquisa da Pecuária Municipal, on October 15, and the Produção Agrícola Municipal , October 20. A series of maps shows its location and changes from 1990 to 2019.